Creación de un programa radial sobre las actividades institucionales de la Universidad Politécnica Salesiana, sede El Girón. - García Mendoza, Gisselle Beatriz (2016)
In this report is possible to appreciate the detailed description of the process which the radio program UPS MAGAZINE, an institutional radio-magazine from Universidad Politécnica Salesiana had to go through, prior to its publication at the University campus community “El Giron”.This program, by focusing on institutional, academic, cultural and sports topics, contributes to the empowerment of the University identity in young students. The participation and inclusion are the main axes about the process of this product, since UPS MAGAZINE represents a spot in which the university can recognize and doing internal dialogues where all people are welcome. Moreover, one of the goals of the radio program is to make the students know about the activities that the institution carries out, due to the lack of them in order to encourage active participation of each member of the UPS. This radio program is the result of a thorough internal investigation process of the institution which determined the informative and communicational needs of the community. UPS MAGAZINE, the radio-magazine, was designed based on young people and their needs, which combines formats and timeless sound resources with useful information in order to strengthen relational links between the institution and students.